The significance of a nominal sentence in Balaghah Perspective in Surah Al-Tawbah and the way to teach it / Dalâlatu Jumlah Ismiyah 'ala Dhau'i al-Balâghah fi Surah at-Taubah wa Tharîqati Ta'lîmihâ - Pulungan, Zubaidah; Hulawa, Djeprin Ersen (Al-Manar, 2022)
ملخّصلاستكشاف ثروة كنوز القرآن يلزم إتقان علم البلاغة. تحرير القرآن قد تم نقله فى تكوين الكلام الخباري والانشائى، والإسمية والفعلية في السور المختلفة، اهتم الباحث بالمناقشة بشكل أعمق حول مشكلة دلالة جملة اسمية على ضوء البلاغة فى سورة التوبة وطريقة تعليمها. موضوع هذا البحث آيات قرآنية من جملة الإسمية. الطريقة المستخدمة في هذا البحث هي تحليل محتويات كتاب (content analysis) ثم وصفها في الجدول. وأظهرت النتائج أن عدد الآيات في سورة التوبة التي تحتوي على الجملة الإسمية أكثر من الجملة الفعلية مما يدل على أن معظم الآيات تنسب صفة واحدة إلى شيء ما، ولا تدل على وقوع حدث في وقت معين. في حين أن طريقة التعلم المناسبة لجملة إسميية كلام خباري هي الطريقة الاستقرائية. ABSTRACT To explore the wealth of the Quran’s treasures, it is necessary to master the science of rhetoric (Balaghah). The editing of the Qur’an has been transmitted in the formulation of informative and constructive speech, nominative and verbal speech in the various surahs. The researcher was interested in discussing in a deeper way the problem of the significance of a nominal sentence in light of the rhetoric in Surah al-Taubah and its teaching method. The subject of this research is Qur’an verses that are nominal. The method used in this research is to analyze the contents of the book (content analysis) and then describe it in the table. The results showed that the number of verses in Surah at-Taubah that contain the nominative sentence is more than the actual sentence, which indicates that most of the verses attribute one adjective to something, and do not indicate that an event occurred at a specific time. Whereas the appropriate learning method for a noun sentence is the inductive method